Phenotypic integration emerges from aposematism and scale in poison frogs - Santos, Juan C. (National Academy of Sciences, 2011)
Complex phenotypes can be modeled as networks of component traits connected by genetic, developmental, or functional interactions. Aposematism, which has evolved multiple times in poison frogs (Dendrobatidae), links a warning signal to a chemical defense against predators. Other traits are involved in this complex phenotype. Most aposematic poison frogs are ant specialists, from which they sequester defensive alkaloids. We found that aposematic species have greater aerobic capacity, also related to diet specialization. To characterize the aposematic trait network more fully, we analyzed phylogenetic correlations among its hypothesized components: conspicuousness, chemical defense, diet specialization, body mass, active and resting metabolic rates, and aerobic scope. Conspicuous coloration was correlated with all components except resting metabolism. Structural equation modeling on the basis of trait correlations recovered “aposematism” as one of two latent variables in an integrated phenotypic network, the other being scaling with body mass and physiology (“scale”). Chemical defense and diet specialization were uniquely tied to aposematism whereas conspicuousness was related to scale. The phylogenetic distribution of the aposematic syndrome suggests two scenarios for its evolution: (i) chemical defense and conspicuousness preceded greater aerobic capacity, which supports the increased resource-gathering abilities required of ant–mite diet specialization; and (ii) assuming that prey are patchy, diet specialization and greater aerobic capacity evolved in tandem, and both traits subsequently facilitated the evolution of aposematism.